A REAPPRAISAL OF THE ITALIAN RECORD OF THE CRETACEOUS PACHYCORMID FISH PROTOSPHYRAENA LEIDY, 1857 (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
The genus Protosphyraena is known mainly from partial remains, consisting of isolated blade-like teeth, conical rostra and scythe-like pectoral fins. This paper provides a new insight into partial specimens of the genus Protosphyraena from the Cretaceous of NE Italy, housed in historical collections from local paleontological museums and previously poorly known to the international scientific community. The specimens are referred to the species Protosphyraena ferox, based on the morphology of the pectoral fin. This attribution is consistent with the paleobiogeographic distribution and stratigraphic range of this taxon. The Italian material provides new information about the distribution in time and space of Protosphyraena, which is relatively poorly known despite being an iconic taxon. The Italian remains, although fragmentary, contribute to fill a gap in the central Tethys record of the genus, whose range probably extended worldwide, considering also the genus Australopachycormus and its profound (possibly congeneric) similarities.